KINERJA KEUANGAN PADA KOPERASI PENERIMA DANA BERGULIR MODAL KERJA DI DAERAH ISTIMEWA YOGYAKARTA Studi Kasus pada Koperasi Serba Usaha (KSU) BMT An Ni’mah Kotagede - Siti Mubiroh; Beni Suhendra Winarso (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2014)
Empowerment of cooperatives is part  of poverty reduction through the expansion of employment opportunities and the increase of society incomes. In the framework of economic empowerment and cooperatives income increasing in DIY, the provincial government provide Dana Bergulir Modal Kerja to increase the production capacity of the cooperative.The objective of this research is to analyze the financial performance of cooperatives before and after receiving Dana Bergulir Modal Kerja. The main data that was collected is secondary data. The financial data was analyzed using quantitave analysis using financial ratio analysis and different t-test (paired sample t test) .Result of analysis showed that there are some increases in  debt to total asset ratio and there is no increase in  current ratio, cash ratio, net profit margin ratio, return on asset ratio and return on equity ratio in KSU BMT An Ni’mah Kotagede after receiving Dana Bergulir Modal Kerja.